Metodología docente y rendimiento académico de estudiantes, Carrera de Pedagogía de las Ciencias Experimentales Matemáticas y la Física UNACH - Caizatoa Llumiquinga, Doris Michelle (2024)
The teaching methodology used in the classroom is considered highly complex and fundamental when dealing with students' academic performance. That is why the objective of this research was to analyze the methodology teachers applied and students' academic performance in the Career of Pedagogy of Experimental Sciences: Mathematics and Physics of the National University of Chimborazo in the period 2023-1S. The methodology applied was a quantitative approach with a non-experimental design at a descriptive level, where field and cross-sectional research were used to obtain information. A survey was applied that was aimed at a sample of 128 students of the Career of Pedagogy of Experimental Sciences: Mathematics and Physics from the National University of Chimborazo; as a result of this survey, it was obtained that the majority of students selected the option of almost always, according to the scale given, considering it good in the investigated career. In the same way, the unique records of the career students were requested to obtain the general average of all the subjects; in this way, it has been possible to know that 83% of the students have a general average higher than 7.